Application and Theory of Petri Nets 33rd International Conference, PETRI NETS 2012, Hamburg, Germany, June 25-29, 2012. Proceedings - Haddad, Serge; Pomello, Lucia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 33rd International Conference on Applications and Theory of Petri Nets and Concurrency, PETRI NETS 2012, held in Hamburg, Germany, in June 2012. The 18 regular papers and 3 tool papers presented were carefully reviewed and selected from 55 submissions. The book also contains 2 invited talks. All current issues on research and development in the area of Petri nets and related models of concurrent systems are addressed.
Keywords: Computer science; Software engineering; Data structures (Computer science).; Logic design; Computer Science; Computation by Abstract Devices; Software Engineering; Logics and Meanings of Programs; Probability and Statistics in Computer Science; Data Structures